2013
DOI: 10.1007/s00508-012-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Migrants and obstetrics in Austria—applying a new questionnaire shows differences in obstetric care and outcome

Abstract: Administration of a standardized questionnaire for assessment of migrant status in obstetric departments in Austria was shown to be feasible. We assessed differences in obstetric care and outcome and consequently recommend that action should be initiated in Austria toward harmonizing obstetric procedures among the migrant and the nonmigrant groups and toward minimizing risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
2
11
1
3
Order By: Relevance
“…The findings of delayed access to prenatal care and reduced number of prenatal visits in the immigrant group could be attributable to differences in health expectations related to prenatal care, unawareness of the options available to immigrants, economic difficulties in accessing healthcare facilities, and/or reduced satisfaction with previous encounters with the system. Some of these factors have been reported in other studies [12,23,26]. The family income was significantly lower among immigrants, but the number of second and third trimester prenatal visits and the attendance of parenthood classes (data not presented) were similar between the groups, indicating that delayed booking of the first appointment is the major factor of concern in this population.…”
Section: Discussionsupporting
confidence: 53%
“…The findings of delayed access to prenatal care and reduced number of prenatal visits in the immigrant group could be attributable to differences in health expectations related to prenatal care, unawareness of the options available to immigrants, economic difficulties in accessing healthcare facilities, and/or reduced satisfaction with previous encounters with the system. Some of these factors have been reported in other studies [12,23,26]. The family income was significantly lower among immigrants, but the number of second and third trimester prenatal visits and the attendance of parenthood classes (data not presented) were similar between the groups, indicating that delayed booking of the first appointment is the major factor of concern in this population.…”
Section: Discussionsupporting
confidence: 53%
“…Our study, however, did not find this difference between immigrants and non-immigrants. An analysis of birth data of approximately 1800 newborns collected prospectively in Austria showed a significant difference only for one sub-group, namely women of Turkish origin, who had fewer elective caesarean deliveries and more vaginal births compared with non-immigrant women [ 25 ]. Several authors have established a higher frequency of emergency caesarean deliveries among immigrants and ethnic minorities in general [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oberaigner et al (2013) [ 25 ] examined whether factors associated with migration affect the frequency of caesareans. Unlike in our analysis, Oberaigner et al identified language proficiency as a relevant parameter: the proportion of vaginal births was significantly higher in the sub-groups of women from ex-Yugoslavia and Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And again: "We ...... recommend that action should be initiated in Austria toward harmonizing obstetric procedures among the migrant and the non-migrant groups and toward minimizing risk factors [25]. If anything, countries which experience sudden influxes of such patients, be they absolute or relative, as in a small population like Malta's, should be at an even greater alert, than countries which have such experiences with slowly increasing migrant populations.…”
Section: Medical Issuesmentioning
confidence: 99%